METHODS AND PRACTICE OF TEACHING ENGLISH AS EIL IN SMA LTI IGM PALEMBANG - Ida Machdarifah (Politeknik Negeri Sriwijaya, 2014)
English as an International Language (EIL) is used for communication in most activities and fields in the world. This encouraged schools in Indonesia to find out the appropriate method and practice in teaching English. SMA LTI IGM had concerned about the use of English teaching methods. This study would find out (1) What were methods and practices/strategies of English applied in teaching and learning English as EIL in SMA IGM Palembang? (2) How did teachers of English improve the students` ability in teaching English at the school? (3) What programs or activities provided from the school to facilitate creating English atmosphere in this school environment? The research finding of English teaching and learning at SMA LTI IGM Palembang was shown from the observation`s result toward the teachers, students and teaching and learning process for one semester. The method of teaching and learning English as EIL applied was English communicative teaching and learning or CLT. Per level class was applied, where the students are grouped based on their same characteristics of English competence, ability and grade. Students` class setting and situation were also classified into per skill class setting where students were taught in the same skill learned. Moreover, the facilities of the school were complete to support the teaching and learning practice process and to fulfill the wide variety of activities used of this technique.